Study on the Effect of Rock Mass Wetting and Drying Cycle on the Mechanical Behavior of Rock-Socketed Piles on Slopes - CAO Ting; HE Liu; WANG Wei; ZHAO Wang; LIU Zhao; ZHONG Junhui (工程科学与技术)
This study focuses on the sandy shale surrounding the rock-socket piles at Luogu Bridge within the Lianghekou reservoir area. The aim is to explore the impact of rock mass weakening on the mechanical behavior of bridge rock-socket piles under wetting and drying cycles. Wetting and drying cycle tests are performed to analyze rock mechanical parameter variations and understand the weakening mechanisms. Employing the generalized Hoek-Brown criterion and finite-difference numerical simulations, the research systematically examines the evolution of the load-bearing behavior of rock-socketed piles across various wetting and drying cycles. The findings reveal that after 28 wetting-drying cycles, the uniaxial compressive strength, Young's modulus, cohesion, and internal friction angle of the rock gradually decrease by 20.82%, 25.97%, 14.83%, and 28.67%, respectively. Simultaneously, Poisson's ratio gradually increases, with a degree of deterioration of 44.13%. The mechanical parameters demonstrate strong correlations with the number of cycles through power and logarithmic functions. Microstructural analysis of the rocks indicates that after 28 cycles, hydration-prone minerals decrease, with mica content reducing from 35.1% to 27.5%, chlorite content from 11.4% to 8.4%, and anorthose content from 25.3% to 14.5%. Scanning electron microscope results highlight significant damage to the rock specimens' microstructure after 28 cycles, including an increase in cracks and pores and an expansion of the dissolution area. The loss of hydration-prone